A novel β-MnO2 micro/nanorod arrays directly grown on flexible carbon fiber fabric for high-performance enzymeless glucose sensing. (20th January 2017) - Weina, Xu; Guanlin, Liu; Chuanshen, Wang; Hu, Chenguo; Wang, Xue
Graphical abstract: Highlights: β-MnO2 is selected as electrode material of enzymeless glucose sensor for the first time. β-MnO2 micro/nanorod arrays directly grown on carbon fiber fabric is obtained by a simple method. The β-MnO2 electrode towards electro-oxidation of glucose exhibits superior sensitivity. Abstract: Intrinsic electrocatalytic activities of a material and electrode architecture for supporting the active material are crucial factors that determine the electrochemical sensing performance. In this work, tetragonal β-MnO2 is taken as an electrocatalytic material for enzymeless glucose sensing. To construct a three dimensional nanostructure electrode, β-MnO2 is directly grown on flexible carbon fiber fabric forming the micro/nanorod arrays (RA). For comparison, β-MnO2 micro/nanorod powder (RP) is immobilized on graphite electrode by Nafion binder. Both β-MnO2 RA and RP electrodes are investigated systematically as enzymeless glucose sensors and the results indicate the high sensitivity of 1650.6 μA mM −1  cm −2, wide linear range up to 4.5 mM for the RA electrode, which shows much better performance than that of RA electrode. The sensitivity of RA electrode towards electro-oxidation of glucose is about 1.7-fold as much as that for RP electrode, mainly benefiting from the favorable electrode architecture. Besides, the RA electrode shows extraordinary stability, reproducibility and selectivity. Our investigation indicates that the electrode based on the β-MnO2 micro/nanorod array directly grown on carbon fiber fabric is outstanding candidate for high efficiency flexible enzymeless glucose sensing.